Chancen und Perspektiven eines neuen Wörterbuchtyps: Das zweisprachige Lernerwörterbuch für Fachsprachen - Fata, Ildikó (HERMES - Journal of Language and Communication in Business, 2011)
The purpose of the present paper is twofold: on the one hand it aims to outline a new type of dictionaries, the LSP dictionary for learners, and distinguish it from other dictionary types; on the other hand the study presents the multifunctional information structure of this type of dictionary through the example of two dictionaries. First the paper examines some formerly suggested names of the new type of dictionary in three languages (Hungarian/German/English). Then the author proposes a new name (chapter 2.1.), this is followed (chapter 2.2.) by the analysis of the more speciﬁc literature on the requirements against multifunctional and user-friendly LSP dictionaries for learners (see Fuertes-Olivera (2005), Tarp (2005), and Fata (2009a)). Finally the author distinguishes this type of dictionaries from other dictionary types and gives a deﬁnition (chapter 2.3.). Since the study is based on the ﬁndings of the modern Danish functional lexicographic theory, the paper applies its concepts: in the ﬁnal section of the theoretical part of the paper the author describes the possible types of users of LSP dictionaries for learners, the potential types of user situations (chapter 2.4.) and the potencial dictionary functions (chapter 2.5.). In the practical part of the study the author presents the macro-, micro- and hyperstructures chosen in relation to the given special subject ﬁeld and LSP in order to make working with learners’ dictionaries easy and enjoyable for the primary target group of the dictionaries: for those who study LSP in a foreign language.